Preferences for Stock Characteristics As Revealed by Mutual Fund Portfolio Holdings - FALKENSTEIN, ERIC G. (Journal of Finance, 1996)
ABSTRACT This investigation of the cross‐section of mutual fund equity holdings for the years 1991 and 1992 shows that mutual funds have a significant preference towards stocks with high visibility and low transaction costs, and are averse to stocks with low idiosyncratic volatility. These findings are relevant to theories concerning investor recognition, a potential agency problem in mutual funds, tests of trend‐following and herd behavior by mutual funds, and corporate finance.